Suicide nucleophilic attack: Reactions of benzohydroxamate anion with bis(2,4-dinitrophenyl) phosphate - Orth, Elisa S.; Da Silva, Pedro L. F.; Mello, Renata S.; Bunton, Clifford A.; Milagre, Humberto M. S. [UNESP]; Eberlin, Marcos N.; Fiedler, Haidi D.; Nome, Faruk (American Chemical Society (ACS), 2009)
(Chemical Equation Presented) The reaction between the benzohydroxamate anion (BHO-) and bis(2,4-dinitrophenyl)phosphate (BDNPP) has been examined kinetically, and the products were characterized by mass and NMR spectroscopy. The nucleophilic attack of BHO- follows two reaction paths: (i) at phosphorus, giving an unstable intermediate that undergoes a Lossen rearrangement to phenyl isocyanate, aniline, diphenylurea, and O-phenylcarbamyl benzohydroxamate; and (ii) on the aromatic carbon, giving an intermediate that was detected but slowly decomposes to aniline and 2,4-dinitrophenol. Thus, the benzohydroxamate anion can be considered a self-destructive molecular scissor since it reacts and loses its nucleophilic ability. © 2009 American Chemical Society.
Keywords: Aromatic carbon; Chemical equations; Dinitrophenol; Dinitrophenyl; Diphenylurea; Molecular scissor; NMR spectroscopy; Nucleophilic attack; Phenyl isocyanates; Reaction paths; Aniline; Chemical reactions; Nuclear magnetic resonance spectroscopy; Phenols; Phosphorus; Urea; Negative ions; 2 phenylcarbamylbenzohydroxamate; 2,4 dinitrophenol; aniline; benzohydroxamic acid; bis(2,4 dinitrophenyl)phosphate; diphenylurea; nucleophile; phenyl isocyanate; phosphorus; unclassified drug; urea derivative; chemical reaction kinetics; decomposition; lossen rearrangement reaction; mass spectrometry; molecular stability; nonhuman; nuclear magnetic resonance spectroscopy; 2,4-Dinitrophenol; Anions; Benzene; Hydroxamic Acids; Kinetics; Magnetic Resonance Spectroscopy; Molecular Structure; Phosphates